ANALISIS SEMIOTIKA PADA IKLAN DAN IMPLIKASINYA DALAM PEMBELAJARAN BAHASA INGGRIS PRODI DESAIN KOMUNIKASI VISUAL - Hening Laksani; Brillindra Pandanwangi (AKSA: Jurnal Desain Komunikasi Visual, 2023)
Technological development affect the communication and information sector in society. Advertising as a means of conveying information is inevitably evolving. This study discusses the study of Ferdinand de Saussure’s Semiotics on commercial and non-commercial advertisement in English. Learning English, as one of the necessary abilities, can be accomplished through the use of materials related to visual design. Utilizing a qualitative descriptive as a research method, this emphasizes not only the description and elaboration on specific meanings in a visual design context, but also the improvement of English abilities. Based on the data analysis, the results of the study showed that there is a concept of advertisement which is influenced by the images and the dictions used in a unified reality. The use of implied and explicit language as well as idiomatic expressions reflect an important element to understand and comprehend the meaning from the visual object. The results of the study indicated the implications for learning English in Communication and Visual Design study program, namely provide more meaningful learning experience to enhance students’ language skills and abilities.